YWHAE Rearrangement in a Purely Conventional Low-grade Endometrial Stromal Sarcoma that Transformed Over Time to High-grade Sarcoma: Importance of Molecular Testing. (September 2018) - Aisagbonhi, Omonigho; Harrison, Beth; Zhao, Liena; Osgood, Rebecca; Chebib, Ivan; Oliva, Esther
Abstract : Low and high-grade endometrial stromal sarcomas (ESS) can be distinguished on a morphologic basis. Low-grade ESS is composed of oval cells that resemble normal proliferative-phase endometrial stroma, while the well-known high-grade ESS is composed of round cells growing in nests separated by delicate sinusoidal vasculature. Recurrent JAZF1 rearrangements have been reported to be most frequent in low-grade stromal sarcomas (up to 60%), while YWHAE rearrangements are characteristic of high-grade ESS. Herein, we report a case of a 45-yr-old woman with stage IA typical low-grade ESS who developed multiple abdominopelvic recurrences and lung metastases 15 mo after her primary tumor was resected. The unusual morphology (without high-grade areas) as well as the aggressive behavior of the tumor prompted molecular testing which showed YWHAE rearrangement in her abdominopelvic recurrence and her primary tumor. Five years after her primary tumor was resected, she developed scalp metastases with a typical morphology of a high-grade ESS associated with t (10;17) and died of her disease. Our case highlights the potential value of molecular testing in all low-grade ESS at time of initial diagnosis to stratify patients at higher risk for developing high-grade ESS with the goal of offering closer follow-up for early detection and treatment if transformation occurs.